2018
DOI: 10.1002/eap.1763
|View full text |Cite
|
Sign up to set email alerts
|

Developing climate‐smart restoration: Can plant microbiomes be hardened against heat waves?

Abstract: Heat waves are increasing in frequency and intensity, presenting a challenge for the already difficult practice of ecological restoration. We investigated whether pre-heating locally sourced rhizosphere soil (inoculum) could acclimatize plants to a field-imposed heat wave in a restoration setting. Soil heating in the laboratory caused a marked shift in rhizosphere bacterial community composition, accompanied by an increase in species evenness. Furthermore, pre-heated rhizosphere soil reduced plant height, numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 84 publications
1
12
0
Order By: Relevance
“…To the Editor -Rapid advances in DNA-sequencing and bioinformatics technologies in the past two decades have substantially improved understanding of the microbial world. This growing understanding relates to the vast diversity of microorganisms; how microbiota and microbiomes affect disease 1 and medical treatment 2 ; how microorganisms affect the health of the planet 3 ; and the nascent exploration of the medical 4 , forensic 5 , environmental 6 and agricultural 7 applications of microbiome biotechnology. Much of this work has been driven by marker-gene surveys (for example, bacterial/archaeal 16S rRNA genes, fungal internaltranscribed-spacer regions and eukaryotic 18S rRNA genes), which profile microbiota with varying degrees of taxonomic specificity and phylogenetic information.…”
Section: Reproducible Interactive Scalable and Extensible Microbiommentioning
confidence: 99%
“…To the Editor -Rapid advances in DNA-sequencing and bioinformatics technologies in the past two decades have substantially improved understanding of the microbial world. This growing understanding relates to the vast diversity of microorganisms; how microbiota and microbiomes affect disease 1 and medical treatment 2 ; how microorganisms affect the health of the planet 3 ; and the nascent exploration of the medical 4 , forensic 5 , environmental 6 and agricultural 7 applications of microbiome biotechnology. Much of this work has been driven by marker-gene surveys (for example, bacterial/archaeal 16S rRNA genes, fungal internaltranscribed-spacer regions and eukaryotic 18S rRNA genes), which profile microbiota with varying degrees of taxonomic specificity and phylogenetic information.…”
Section: Reproducible Interactive Scalable and Extensible Microbiommentioning
confidence: 99%
“…Stress events can exert a strong negative impact on soil biota, and it should not be assumed that subjecting soil microbial communities to a stressor will always result in increased resilience or improved plant performance (Millar & Bennett, 2016). In some instances, stress events could result in an inferior soil microbial community with detrimental impacts plant growth (Compant, Van Der Heijden, & Sessitsch, 2010; Rubin et al., 2018). For example, environmental stressors could reduce the abundance or activity of beneficial soil micro‐organisms or increase plant susceptibility to soil pathogens.…”
Section: Limitations Risks and Outstanding Questionsmentioning
confidence: 99%
“…there are few examples from natural systems. One recent study byRubin et al (2018) explored whether or not soil microbial communities could be hardened against heat waves in order to develop 'climate-smart' restoration practices.…”
mentioning
confidence: 99%
“…Despite the recognized importance of temperature and microbial symbionts in resistance to infection, few studies have explored the effects of temperature on the microbiome, and the consequences of these effects for disease resistance have seldom been considered at all. Landscape surveys and experimental manipulations have shown that temperature can be an important driver of microbial community composition and function in soils and aquatic environments (Steinauer et al, 2015;Chiriac et al, 2017;Rubin et al, 2018). Exposure of rhizosphere communities to high temperatures can lead to loss of taxa and alterations in the ability of soils to support plant growth and suppress disease (van der Voort et al, 2016;Rubin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Landscape surveys and experimental manipulations have shown that temperature can be an important driver of microbial community composition and function in soils and aquatic environments (Steinauer et al, 2015;Chiriac et al, 2017;Rubin et al, 2018). Exposure of rhizosphere communities to high temperatures can lead to loss of taxa and alterations in the ability of soils to support plant growth and suppress disease (van der Voort et al, 2016;Rubin et al, 2018). In insects, experimental temperature elevations reduced populations of endo-and ectosymbionts (Parkinson et al, 2014;Kikuchi et al, 2016), suggesting that fever and high temperature could be costly for host-symbiont mutualisms and their role in resistance to infection.…”
Section: Introductionmentioning
confidence: 99%